Body Dissatisfaction sebagai Prediktor Kesejahteraan Psikologis pada Siswa SMA Negeri 21 Medan - Nani Barorah Nasution; Fetrayana Gultom (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2026)
This study aims to examine the effect of body dissatisfaction on the psychological well-being of students at SMA Negeri 21 Medan. A quantitative method with simple linear regression analysis was employed. A sample of 274 students was selected using proportional stratified random sampling from grades X, XI, and XII. The normality test using the Kolmogorov-Smirnov method yielded a significance value of 0.095 > 0.05, and the linearity test showed a deviation from linearity value of 0.215 > 0.05, confirming both assumptions were met. The results of the simple linear regression analysis yielded the equation Y = 141.505 – 0.349X. The t-test results showed that body dissatisfaction has a significant negative effect on psychological well-being with t = -6.907 and significance (p) < 0.001 < 0.05, indicating that the research hypothesis is accepted. The coefficient of determination (R²) was 0.149, meaning that body dissatisfaction contributes 14.9% to the variance in psychological well-being, while the remaining 85.1% is influenced by other factors not examined in this study. Categorization results revealed that 58.4% of respondents had high levels of body dissatisfaction, while 87.2% of respondents demonstrated high levels of psychological well-being. Therefore, it can be concluded that the higher the level of body dissatisfaction experienced by students, the lower their psychological well-being.